6=2-4m

Simple and best practice solution for 6=2-4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=2-4m equation:


Simplifying
6 = 2 + -4m

Solving
6 = 2 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
6 + 4m = 2 + -4m + 4m

Combine like terms: -4m + 4m = 0
6 + 4m = 2 + 0
6 + 4m = 2

Add '-6' to each side of the equation.
6 + -6 + 4m = 2 + -6

Combine like terms: 6 + -6 = 0
0 + 4m = 2 + -6
4m = 2 + -6

Combine like terms: 2 + -6 = -4
4m = -4

Divide each side by '4'.
m = -1

Simplifying
m = -1

See similar equations:

| 4*5=10x | | x-4=2x+56 | | 4x+11=41-6x | | 6-8x=-2.6 | | x^5-x^2+4=0 | | -20v=100 | | -3(x+2)+2x=16 | | 2w^2=-13w-21 | | -4x-(-16)=240 | | x^2+4x+8=16 | | X-(x-7)=3 | | -14-x=9-5x+4x | | -(x+2)+2x=16 | | 6(-6+3x)=180 | | 5x^2-4x=10 | | 3(8-x)=15 | | b^2=-14b-48 | | x+35=3x-9 | | 2m+3(m-9)=2(m+3) | | -234=6(-8+5k)-6 | | 5x+6=-78-7 | | 3-(-5x)=11 | | 5x+6=78-7x | | 7(4+5x)=-42 | | 3.5y+15=17 | | -52-2x=12-10 | | 60c=123 | | 9m^2=3m+2 | | 8n+16.2=-8.48 | | 3u=-31 | | x^2-114x+2520=0 | | x^3-3x^2= |

Equations solver categories